Analisis Kadar Kalsium pada Kulit Pisang Ambon dan Pisang Raja dengan Metode Spektrofotometri Serapan Atom - Margaretha Margaretha; Pratiwi Apridamayanti; Hadi Kurniawan (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Indonesia is one of the countries known as the world's banana producer. Banana is one of the local fruits that are widely spread in Pontianak, West Kalimantan. Ambon banana and raja banana are classified as bananas that can be consumed directly, so banana peels are often discarded and considered as waste. Whereas banana peels are rich in nutrients such as macro and micro minerals. The purpose of this study was to determine the mineral levels of calcium in the peels of ambon banana and raja banana. Sample preparation using dry digestion method with 0.5 M HNO3 solvent. Method verification was carried out with parameters of linearity, LOD, LOQ, precision and accuracy. The assay was carried out with atomic absorption spectrophotometry at a wavelength of 422.67 nm. The results showed that the mineral levels of calcium in the wet peels of ambon banana are 104.29 mg/kg and raja banana are 314.79 mg/kg. Based on the research conducted, it can be concluded that the levels of calcium mineral in raja banana peels are higher than ambon banana peels